156k views
3 votes
2(6-2x)-2x=2(5+x)-4 value of x?

User Vloxxity
by
5.4k points

2 Answers

1 vote

Answer:

x= 3/4

Explanation:

I looked it up. Hope this helps

User Todd Chambery
by
5.1k points
4 votes

Answer:

x =
(3)/(4)

Explanation:

Given

2(6 - 2x) - 2x = 2(5 + x) - 4 ← distribute parenthesis on both sides

12 - 4x - 2x = 10 + 2x - 4 ← simplify both sides

12 - 6x = 6 + 2x ( subtract 2x from both sides )

12 - 8x = 6 ( subtract 12 from both sides )

- 8x = - 6 ( divide both sides by - 8 )

x =
(-6)/(-8) =
(3)/(4)

User Andy Tschiersch
by
5.8k points